Juristic Concept of the Validity of Statutory Law A Critique of Contemporary Legal Nonpositivism - Grabowski, Andrzej; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book presents the theory of the validity of legal norms, aimed at the practice of law, in particular the jurisdiction of the constitutional courts. The postpositivist concept of the validity of statutory law, grounded on a critical analysis of the basic theories of legal validity elaborated up to now, is introduced. In the first part of the book a contemporary German nonpositivist conception of law developed by Ralf Dreier and Robert Alexy is analysed in order to answer the question whether the juristic concept of legal validity should include moral standards or criteria. In the second part, a postpositivist concept of legal validity and an innovative model of validity discourse, based on the juristic presumption of the validity of legal norms, are proposed. The book is a work on analytical legal theory, written from a postpositivist, detached point of view.
Keywords: Law; Language and languages -- Philosophy; Political science; Law -- Philosophy; Constitutional law; Law; Theories of Law, Philosophy of Law, Legal History; Fundamentals of Law; Constitutional Law; Philosophy of Law; Philosophy of Language; Electronic books